Strengthening lung cancer screening in Europe: fostering participation, improving outcomes, and addressing health inequalities through collaborative initiatives in the SOLACE consortium - Kauczor, Hans-Ulrich; Stackelberg, Oyunbileg von; Nischwitz, Emily; Chorostowska-Wynimko, Joanna; Hierath, Monika; Mathonier, Coline; Prosch, Helmut; Zolda, Pamela; Revel, Marie-Pierre; Horváth, Ildikó; Vašáková, Martina Koziar; Powell, Pippa; et al. (Insights into imaging, 2024)
The Strengthening the Screening of Lung Cancer in Europe (SOLACE) initiative, supported by Europe’s Beating Cancer Plan, is dedicated to advancing lung cancer screening. This initiative brings together the most extensive pan-European network of respiratory and radiology experts, involving 37 partners from 15 countries. SOLACE aims to enhance equitable access to lung cancer screening by developing targeted recruitment strategies for underrepresented and high-risk populations. Through comprehensive work packages, SOLACE integrates scientific research, pilot studies, and sustainability efforts to bolster regional and national screening efforts across EU member states.
Gesehen am 23.04.2025